2016
DOI: 10.1002/14651858.cd007628.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for female pattern hair loss

Abstract: Although there was a predominance of included studies at unclear to high risk of bias, there was evidence to support the efficacy and safety of topical minoxidil in the treatment of FPHL (mainly moderate to low quality evidence). Furthermore, there was no difference in effect between the minoxidil 2% and 5% with the quality of evidence rated moderate to low for most outcomes. Finasteride was no more effective than placebo (low quality evidence). There were inconsistent results in the studies that evaluated las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
60
0
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 103 publications
1
60
0
8
Order By: Relevance
“…Subsequently, with regard to FPHL, a systematic review involving 1242 female subjects, with an observation period of 24-32 weeks, that analyzed eight RCT using 1%, 2% and 5% minoxidil showed the efficacy of minoxidil. 65 In the minoxidil group, the number of hairs in a 1-cm 2 area of hair loss increased by a mean of 13.18 (95% CI, 10.92-15.44) compared with the placebo group. With regard to adverse events, the results of an analysis of four RCT with 725 subjects showed that the relative risk was 1.12 (95% CI, 0.61-2.06), 1.24 (95% CI, 0.82-1.87) and 2.05 (95% CI, 0.96-4.37) for the 1%, 2% and 5% minoxidil groups, respectively.…”
Section: Cq3: Is Topical Application Of Minoxidil Effective?mentioning
confidence: 89%
See 4 more Smart Citations
“…Subsequently, with regard to FPHL, a systematic review involving 1242 female subjects, with an observation period of 24-32 weeks, that analyzed eight RCT using 1%, 2% and 5% minoxidil showed the efficacy of minoxidil. 65 In the minoxidil group, the number of hairs in a 1-cm 2 area of hair loss increased by a mean of 13.18 (95% CI, 10.92-15.44) compared with the placebo group. With regard to adverse events, the results of an analysis of four RCT with 725 subjects showed that the relative risk was 1.12 (95% CI, 0.61-2.06), 1.24 (95% CI, 0.82-1.87) and 2.05 (95% CI, 0.96-4.37) for the 1%, 2% and 5% minoxidil groups, respectively.…”
Section: Cq3: Is Topical Application Of Minoxidil Effective?mentioning
confidence: 89%
“…With regard to adverse events, the results of an analysis of four RCT with 725 subjects showed that the relative risk was 1.12 (95% CI, 0.61-2.06), 1.24 (95% CI, 0.82-1.87) and 2.05 (95% CI, 0.96-4.37) for the 1%, 2% and 5% minoxidil groups, respectively. 65 In a systematic review involving 631 female subjects with an observation period of 26-52 weeks that analyzed three RCT on 2% and 5% minoxidil, the total number of hairs in a 1-cm 2 area of hair loss was smaller with a mean of 2.12 (95% CI, 5.47-1.23) in the 2% minoxidil group than the 5% minoxidil group, but no significant difference was found between the two groups. 65 With regard to adverse events, the results of an analysis of four RCT with 1006 subjects also showed that the relative risk was 1.02 (95% CI, 0.91-1.20), and no significant difference was found between the two groups.…”
Section: Cq3: Is Topical Application Of Minoxidil Effective?mentioning
confidence: 99%
See 3 more Smart Citations